Improving Activity and Learning Outcomes in Islamic Religious Education through the Use of Animated Video Media for Junior High School Students - Reski Wulandari; Muhammad Ilham; Jumarddin La Fua; Faldin Baen (Dirasah: Jurnal Pendidikan Islam, 2025)
Teaching Islamic Religious Education (IRE) in secondary schools often faces challenges related to students’ low interest and understanding, especially when the material taught is abstract. This study aims to analyze the effectiveness of animation-based video learning media in improving students’ learning outcomes and engagement in IRE lessons. The research employed a Classroom Action Research design conducted in two cycles involving 37 seventh-grade students of SMP Negeri 4 Kendari. Data were collected through observations, learning achievement tests, and documentation, and analyzed using descriptive quantitative and qualitative methods. The results showed a significant increase in teacher activity from 70% to 86.66% and student activity from 63.33% to 86.66%. The class average score improved from 73.33 in the pre-cycle to 93.24 in the second cycle, with overall mastery reaching 89.19%. The findings indicate that animated videos effectively bridge the understanding of abstract concepts, motivate students to participate more actively, and create an engaging and participatory learning atmosphere. This study underscores the importance of integrating visual-audio media into IRE learning and contributes to the literature on the effectiveness of digital media in religious education. The implications suggest that IRE teachers are encouraged to adopt animation-based videos as an innovative teaching strategy, while future research could explore the long-term effects on students’ affective and psychomotor domains.